Au J.S. McLean Centre for Indigenous + Canadian Art à l’Art Gallery of Ontario, une proposition curatoriale pour la souveraineté autochtone - Yiannaki, Daphnée (Muséologies, 2026)
Is it possible to promote a form of Indigenous sovereignty in art museums? This article examines the elements that make it possible to achieve this result in a permanent exhibit of a collection of Indigenous and Canadian art, by considering the exhibition inaugurated in 2018 at the J.S. McLean Centre at the Art Gallery of Ontario. A concrete example of the concept of curatorial activism and of the ethical space of engagement, the curatorial approach brought forward by Wanda Nanibush and Georgiana Uhlyarik highlights a rare paradigm shift within the museum complex. Referring to the textual media in the galleries, the presence of Indigenous languages, the selection of works and artists, the manner of their presentation and the exhibition catalogue, we will show how the exhibition is rooted in Indigenous territory, specifically that of the Anishinaabe. While the exhibition contributes to consolidating and highlighting a canon of Indigenous art, one element undermines this manifestation of radicality and sovereignty: the rotation of works.